Lysyl oxidase inhibitors in colorectal cancer progression - Muxian Liu; Jie Wang; Meihong Liu (Translational Oncology)
The lysine oxidase (LOX) family, consisting of LOX and LOX-like-1–4 (LOXL1–LOXL4), catalyses the cross-linking reaction of collagen and elastin in the extracellular matrix (ECM). Numerous studies have demonstrated that LOX family members are dysregulated in a variety of cancers, including colorectal cancer (CRC), and play a key role in cancer cell migration, proliferation, invasion and metastasis. Targeting LOX family proteins with specific inhibitors has therefore been developed as a new therapeutic strategy for cancer. In this paper, we review the role of LOX enzymes in the development and progression of CRC. In addition, we address recent advances in the development of LOX/LOXL inhibitors, highlighting the potential use of this inhibitor as an effective and complementary treatment for CRC.